(untitled) (Plant Tissue Culture and Biotechnology, 2020)
Poor growth of bulblet and ontogenic development are the major problems of adventitious bulb production of lilies in vitro through explant culture. Ontogenic development from the juvenile phase to the adult vegetative phase strongly correlates with bulblet growth of lily, and it is important to understand how lily bulblets grow in vitro. This study was at aimed to determining an effective in vitro culture process for lily to track bulblet growth, ontogenic development, and bulb production. In the results, bulblet performance was higher with the increase in the amount of medium; however, bulblet size was not satisfactory and was in the juvenile phase under an inducing condition. The threshold weight at which 100% ontogenic development was about 300 mg. Avoiding depletion of sucrose in the media is the key to achieving desired bulblet growth and ontogenic development in vitro and indicates growth could be sustained by subculture. The circumference of bulblets increases with its weight after subcultured in vitro. Therefore, a threshold circumference of about 3.2 cm in proportion to bulblet fresh weight of 300 - 350 mg may be an indicator of ontogenic development. Plant Tissue Cult. & Biotech. 30(1): 1-13, 2020 (June)